SURGICAL LIGATION OF PATENT DUCTUS ARTERIOSUS IN A NONCARDIAC SURGICAL CENTRE - Haq, Anwar -ul-; ullah, Ubaid; ullah, Sami; Javeria, Javeria; Neelofar, Neelofar; Abbasi, M. Zaheer (Journal of Ayub Medical College Abbottabad, 2009)
Background: Surgery for Patent Ductus Arteriosus (PDA) is usually performed in specialized cardiac centres with either open surgery or percutaneous embolisation using different materials and devices. This involves high cost of treatment especially for those poor patients who have grown up to several years of age without seeking any treatment for their disease. The objective of this study is to evaluate the safety of surgery for PDA in a non cardiac paediatric surgical setup. Methods: A total of 89 patients of 8 months to 12 years (mean 3 years) age were operated over a period of 13 years (from 1993 to 2006). Fifty-five cases were females and 34 were males. Investigations included x-ray chest, ECG and echocardiography. All patients with PDA were included in the study except those who had other associated cardiac anomaly and those who had a calcified ductus. The ductus was dissected out and ligated with non-absorbable suture (Silk No. 1 or 2). The patients were discharged by the 5th postoperative day. Results: In majority of the patients the recovery was smooth and uneventful. Eight patients had minor complications which were treated conservatively. There were 3 mortalities in this series; 2 patients were over 10 years of age and had calcified ductus. They died during surgery due to primary haemorrhage and 1 died after 24 hours in the intensive care unit. All patients were reviewed at 1 week, 1 month, 3 months and 1 year after surgery. In majority, the typical machinery murmur disappeared immediately or a soft systolic murmur persisted for up to 4 weeks and then disappeared. Conclusion: With proper patient selection, the procedure can safely be performed in a paediatric surgical setup with facilities for cardiac monitoring. The surgeon needs to receive some additional training in the cardiac institution for safe surgery on these children. This will significantly reduce the cost with minimal complications especially for those poor patients who cannot afford the modern procedures due to monitory constraints. Children older than 10 years are not suitable for open surgery because of calcification of the duct. Keywords: Patent ductus arteriosus, surgical ligation, cardiac surgery